IMPLEMENTASI PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 105 PEKANBARU - Anggi Fitri Chaniago (INSPIRAMATIKA, 2019)
ABSTRAK The current learning system is still dominant with the term learning which is defined as activities such as sitting, listening, record and then go home to be memorized. To avoid and anticipate the saturation, it is necessary to form an important concept that must be implemented in the practice of learning. One of them is contextual teaching and learning. Soetomo (1993: 68) suggests that learning is a process of environmental management of a person who deliberately done so as to enable him to learn to perform or display certain behaviors as well. Ros Effendi, (1980: 148). Learning mathematics means studying human thoughts, which relate to ideas, processes and reasoning. Keywords: Contextual, Learning and Learning Mathematics